КЕЛЕШЕГИМИЗДИ БЕЛГИЛЕЎШИ ТИЙКАРҒЫ ҲҮЖЖЕТ - Абатов, А. (FAN va JAMIYAT, 2018)
The article deals with the description the Strategy of actions in five priority directions of the development of the Republic of Uzbekistan in 2017-2021 and its role in the development of our state.